2021
DOI: 10.3390/genes12060949
|View full text |Cite
|
Sign up to set email alerts
|

Associations of MC4R, LEP, and LEPR Polymorphisms with Obesity-Related Parameters in Childhood and Adulthood

Abstract: MC4R, LEP, and LEPR genes are involved in the hypothalamic leptin-melanocortin regulation pathway, which is important for energy homeostasis. Our study aimed to evaluate the associations between the MC4R rs17782313, LEP rs7799039, and LEPR rs1137101 polymorphisms with obesity-related parameters in childhood and adulthood. The data were obtained from the Kaunas Cardiovascular Risk Cohort study, which started in 1977 with 1082 participants aged 12–13 years. In 2012–2014, the follow-up survey was carried out. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
2
5
0
1
Order By: Relevance
“…However, it must be considered that the prevention and treatment of childhood obesity is a complex task. Additionally, it is known that this disease is of polygenic origin, and other genes are also associated with it, including MCR4 , LEP , FTO, and TMEM18 [ 14 , 32 ]. Knowing that increasing levels of physical activity is an important part of the process, we should mention mechanisms for promoting a more active lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be considered that the prevention and treatment of childhood obesity is a complex task. Additionally, it is known that this disease is of polygenic origin, and other genes are also associated with it, including MCR4 , LEP , FTO, and TMEM18 [ 14 , 32 ]. Knowing that increasing levels of physical activity is an important part of the process, we should mention mechanisms for promoting a more active lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Исследования ассоциации полиморфных вариантов генов лептина и лептинового рецептора с риском развития ожирения в основном проводились с участием взрослых, и их результаты противоречивы [27]. В России ассоциацию вариантов гена рецептора лептина с развитием детского ожирения у девочек изучали К.Д.…”
Section: обоснованиеunclassified
“…The results of a follow-up study involving 1082 participants aged 12–13 years showed that skinfold thickness was associated with gene variants being lower in children with the MC4R TT genotype and the LEP AG genotype, but no associations were found with BMI [ 132 ].…”
Section: Molecular Control In Obesitymentioning
confidence: 99%